KARAKTERISTIK FISIK DAN KIMIA MIE ANTIOKSIDAN DARI PATI SAGU DENGAN EKSTRAK KULIT BUAH NAGA MERAH - Pratiwi, Yuliani; Rahim, Abdul; Hutomo, Gatot S. (AGROTEKBIS, 2016)
The objective of this research was to figure out the physical and chemical characteristic of antioxidant noodle and sago starch with peels extract of red dragon fruit. The reseach design was used Completely Randomized Design with six treatment and triplicate in order to obtain 18 units of trials. The treatment that have been tried namely sago paste that mixed into sago starch that consist of six levels : 100 g; 110 g; 120 g; 130; 140 g dan 150 g. The observation variable that to done including water content, water holding capacity (WHC) and oil holding capacity (OHC), cooking loss and antioxidant content. The data were analysed with analysis of variance and continued with further test of honestly significance difference (HSD) 5%. The result of research shown that the water content tend to increase with the increased of sago starch. Cooking loss tend to increase with increased amount sago starch (110 to 150 g). The antioxidant properties of the noodles are best obtained in the treatment of sago starch 100 g. Â Key Words: Antioxidants, noodles, peels of red dragon fruit, sagu starch.